Last of the Belles the F. Scott Fitzgerald story. ([Place of publication not identified] Digiview Productions, 2004)
This film was made due to the surge of interest in F. Scott Fitzgerald after the release of the theatrical film The Great Gatsby starring Robert Redford. Last of the Belles is a biographical drama depicting the courtship of Fitzgerald and his wife Zelda. The young writer is struggling with writer's block, while his wife comes to a harsh realization about her longtime dream of becoming a ballerina. The couple find out that through all their personal demons and hardship, there lies a genuine connection and love between them to overcome all adversity.
DVD ; Standard Full Frame.
Richard Chamberlain, Blythe Danner, Susan Sarandon, David Huffman.
Suitable for all ages.
In English.
Keywords: Biographical films